Kecerdasan Ganda Siswa SMA dan Hubungannya dengan Prestasi Akademik IPA - Mark Gerald B. Doblon (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aims to investigate senior high school students’ multiple intelligences and their academic achievement in science. Methodology: This study employs a descriptive correlational research design. The respondents of this study were 300 in the 11th Grade of senior high school students. The Multiple Intelligences Inventory is used to assess students' intelligence, while their final grade in science measures academic achievement. Main Findings: The results of this study showed that senior high school students possess all intelligence to a great extent. Existential intelligence obtained the highest mean score of 3.96, as possessed by the respondents. On the other hand, musical intelligence got the lowest mean score of 3.60. It also showed that all multiple intelligences correlate with academic performance achievement. The correlation analysis showed that all multiple intelligences were statistically significant and could positively predict academic achievement in science. Novelty/Originality of this study: This present study may give insights to teachers about integrating multiple intelligences in the classroom.